PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARWAYAN PADA PT BHUMYAMCA SEKAWAN - Muhamad Ridho Kurnianto; Imam Muhtadin (Taksasila Edukasi Insani, 2025)
This study aims to analyze the extent to which leadership style and work motivation influence employee performance at PT Bhumyamca Sekawan. Employee performance is a critical element in achieving organizational goals and is affected by various factors, including the leadership approach adopted and the level of individual work motivation. The research employed a quantitative method with an associative approach. Data were collected through the distribution of questionnaires to employees and analyzed using multiple linear regression techniques.The analysis results indicate that: (1) Leadership style has a positive and significant influence on employee performance, as evidenced by a t-value of 2.848, which is greater than the t-table value of 2.000, and a significance value of 0.007, which is less than 0.05. (2) Work motivation also has a positive and significant impact on performance, with a t-value of 2.813 t-table 2.000 and a significance value of 0.006 0.05. (3) Simultaneously, leadership style and work motivation significantly affect employee performance, as indicated by an F-value of 29.189, which exceeds the F-table value of 3.11, and a significance level of 0.000 0.05. Keywords : Leadership Style, Work Motivation, Employee Performance